2006
DOI: 10.1136/hrt.2005.079970
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy: a strong risk factor for pulmonary hypertension in patients with thalassaemia

Abstract: Objective: To determine the association between splenectomy and pulmonary hypertension in patients with thalassaemia with anaemia. Design: Prospective cross-sectional study. Methods: 68 patients with thalassaemia, who had a haemoglobin concentration of less than 100 g/l, were recruited into this study. Echocardiography was performed before clinical data were reviewed. Pulmonary artery pressure was estimated by measuring the systolic transtricuspid pressure gradient from tricuspid regurgitation and adding it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 23 publications
5
61
2
1
Order By: Relevance
“…46 The association of PH with splenectomy and a hypercoagulable state also has been well described in the literature. 17,22,24,26 On the basis of our data, risk of a high TRV with age does not increase in nonsplenectomized patients, an observation not previously described. Circulating RBC-derived microvesicles found to be elevated in splenectomized thalassemia patients may play a role.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…46 The association of PH with splenectomy and a hypercoagulable state also has been well described in the literature. 17,22,24,26 On the basis of our data, risk of a high TRV with age does not increase in nonsplenectomized patients, an observation not previously described. Circulating RBC-derived microvesicles found to be elevated in splenectomized thalassemia patients may play a role.…”
supporting
confidence: 80%
“…7,12 The etiology of PH in thalassemia is multifactorial, involving a complex interaction of platelets, the coagulation system, erythrocytes, and endothelial cells along with inflammatory and vascular mediators. 13,19 Contributing mechanisms include oxidative stress, 20 hemolysis, 21,22 thrombosis, [23][24][25] splenectomy, 17,22,26 abnormal arginine-nitric oxide bioavailability, 13,21 red cell membrane pathology, 27 and iron overload. 28 Although overlap in pathways contributing to vasculopathy and PH is expected in all forms of thalassemia, 13 the pathophysiology of PH is fundamentally different in patients with TI compared with TM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies relying solely on echocardiographic parameters reported prevalence rates ranging between 10% and 78.8% (averaging ≈30%). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The diagnosis was usually established based on a TRV exceeding 2.5-2. study, the prevalence of PAH was considerably lower when more strict echocardiographic criteria and confirmatory right heart catheterization were used. Owing to the systematic approach undertaken in our study, we believe that estimates presented in this report are more likely representative of the true PAH prevalence in patients with β-thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…Poor treatment of thalassemia leads to low hemoglobin concentrations and more splenectomy. Patients with regular blood transfusion and appropriate iron chelation have a low incidence of splenomegaly and are less likely to develop PAH (20).…”
Section: Discussionmentioning
confidence: 99%